Conocimientos sobre factores de riesgo fisiológicos asociados a las malformaciones congénitas en mujeres en edad fértil que acuden a la consulta externa de gineco obstetricia del Hospital Isidro Ayora de la ciudad de Loja, noviembre 2019 – marzo 2020 - Cueva Cueva, Silvia Karina (2020)
Congenital malformations are birth defects that affect the normal development of the fetus; they are a global public health problem with a high rate of neonatal mortality. In pregnancy, risk factors such as nutritional status, maternal infections and chronic maternal diseases can trigger malformations at the level of organs and systems, such as: the nervous system, digestive system, brain, heart, lungs and extremities, by putting the life of the child at risk. The present study is of a descriptive, transversal, quantitative and prospective type, with the purpose of identifying the knowledge about physiological risk factors in women of fertile age in the HIAL's obstetrics and gynecology outpatient clinic, to whom a survey was applied, the data was processed in Microsoft Office Excel, and for its analysis it was used a score that determines the level of knowledge: very high, high, medium, low and very low, depending on the score reached. According to the results obtained, most of the respondents have a good knowledge (83.5%) about physiological risk factors, and a small percentage (2%) showed cases of congenital malformations. Therefore, it is concluded that the population of study presented a very high level of knowledge (97%) about the topic addressed, which can contribute to the reduction of this problem. Keywords: Nutritional status, maternal infections, chronic maternal diseases, prevention, care and control.